Sosialisasi Pelaksanaan Perjanjian Bagi Hasil Tanah Pertanian Antara Pemilik Lahan Dan Penggarap Di Desa Cipadang Kecamatan Gedongtataan Kabupaten Pesawaran - Sumarja, FX; Tisnanta, HS; Triono, Agus; Akib, Muhammad; Tripomo, Petrus (Nemui Nyimah, 2024)
The agricultural land sharecropping agreement is a legal action regulated by Law Number 2 of 1960 concerning Sharecropping Agreements, which originates from customary law in Indonesia. The sharecropping agreement practiced in Cipadang Village, Gedongtataan Subdistrict, Pesawaran Regency has been conducted orally based on trust and mutual agreement. The aim of this activity is to increase the public's understanding of the importance of creating written sharecropping agreements and to provide knowledge of the law that regulates these agreements. As a result, the target audience gains the knowledge and ability to create sharecropping agreements and apply Law Number 2 of 1960. The final evaluation shows a relatively small increase in the public's legal knowledge and understanding, from 60.20 to an average of 78.50. However, according to the extension team, this result is considered outstanding, given that the community's average education level is at the secondary school level. The activities in Cipadang Village should continue to foster legal knowledge, understanding, and public awareness, especially given that there are other questions beyond the topics being socialized. Regarding written sharecropping agreements, most are not authenticated by the village head. For the community, it is sufficient if the agreement is signed by both parties and witnessed by representatives of each side. The share is typically divided equally, 1:1, with costs shared between both parties.